INFLUENCE OF RECUPERATION ENVIRONMENT ON CHRONIC PAIN IN ELDERLY PATIENTS : Received: 04th May 2021; Revised: 27th November 2021, 21st December 2021, 25th January 2022; Accepted: 26th January 2022 - Jingjing, Sun (LIFE: International Journal of Health and Life-Sciences, 2022)
Chronic pain is a common disease of elderly patients, and it is also a factor that has a significant impact on the physical, mental health, and quality of life of elderly patients. In terms of the existing research, most of the relevant fields focus on the diagnosis and treatment of chronic pain, and various alternative therapies have also been studied and discussed on a certain scale. This paper is more from the overall rehabilitation work of medical institutions, for patients with chronic pain, this paper analyzes the factors which influence, not only consider a patient’s nursing intervention but also considers the patient’s medical workplace environment, etc., for a variety of factors, affect the elderly patients with chronic pain conditions and corresponding protection measures are analyzed.